PENGARUH EFIKASI DIRI DAN UPAYA TERHADAP NIATAN BERHENTI DENGAN MEDIASI KINERJA, KEPUASAN KERJA DAN SINDROM KELELAHAN - Desi Purnama Sari; Edi Purwanto (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2018)
The purpose of this study to examines (1) whether the turnover intention is influenced by job performance, job satisfaction and employee burnout; (2) whether job performance is influenced by self-efficacy and efforts; (3) whether job satisfaction is influenced by self-efficacy and efforts; and (4) whether burnout is influenced by self-efficacy. The study is conducted at PT. XYZ with the respondents are 102 staffs at the Station and Service Hub in Soekarno-Hatta International Airport, Terminal 2 and 3, Cengkareng. The analysis technique of this study uses Structural Equation Modeling (SEM) with SmartPLS 2.0 tools. The results of the study have proven that the turnover intention is influenced by job performance and burnout, but it is not proven that the turnover intention is influenced by job satisfaction. It is also proven that job performance is influenced by self-efficacy and efforts. Job satisfaction is also proven to be influenced by self-efficacy, but job satisfaction is not proven influenced by efforts. Finally it is proven that burnout is influenced by self-efficacy.